THE ROLE OF TECHNOLOGY IN MODERN EDUCATION (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role and significance of technology in the modern education system. The use of technology in the educational process creates opportunities to make the learning process more effective and interactive. It demonstrates how technological tools can enhance the content of education, facilitate interactive lessons, and offer opportunities for distance learning for both teachers and students. Additionally, it explores how technology helps develop students' creativity and critical thinking skills and the possibilities of integrating with global educational systems.